2016
DOI: 10.1007/s11192-016-2080-5
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of university units as a multi‐level process. Credibility cycles and resource dependencies

Abstract: This paper presents an analysis of resource acquisition and profile development of institutional units within universities. We conceptualize resource acquisition as a twolevel nested process, where units compete for external resources based on their credibility, but at the same time are granted faculty positions from the larger units (department) to which they belong. Our model implies that the growth of university units is constrained by the decisions of their parent department on the allocation of professori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In its original presentation (Latour and Woolgar 1986) the CC was introduced to characterize the drivers and patterns in the behavior of individual researchers in a molecular biology laboratory. Although the authors have never claimed universal validity, the science studies literature has adopted the CC as a rather generic analytical tool to describe the behavior of researchers or research groups (Hessels and van Lente 2011;Lepori et al 2016). Our analysis has shown that more culture-specific models are required to do justice to the epistemic dimensions of the CC.…”
Section: Variation In Valuationmentioning
confidence: 95%
See 1 more Smart Citation
“…In its original presentation (Latour and Woolgar 1986) the CC was introduced to characterize the drivers and patterns in the behavior of individual researchers in a molecular biology laboratory. Although the authors have never claimed universal validity, the science studies literature has adopted the CC as a rather generic analytical tool to describe the behavior of researchers or research groups (Hessels and van Lente 2011;Lepori et al 2016). Our analysis has shown that more culture-specific models are required to do justice to the epistemic dimensions of the CC.…”
Section: Variation In Valuationmentioning
confidence: 95%
“…Although the CC focuses in its original presentation on the activities of individual researchers, in this paper we apply the model to research groups. The cyclical process of accumulating credibility at this level can also be understood in terms of the CC, since it boils down to the same principles as on the individual level (Leišytė 2007;Lepori et al 2016).…”
mentioning
confidence: 99%
“…For more in-depth discussions and detailed information on the project and on the construction of the instrument, please refer to previous articles of the authors (Probst, Lepori, & Ingenhoff, 2010;Probst, Lepori, De Filippo, & Ingenhoff, 2011;Lepori et al, 2011;Lepori, Probst, & Ingenhoff, 2012;Buhmann et al, 2015;Wise, Lepori, Ingenhoff, & Buhmann, 2015;Lepori, Wise, Ingenhoff, & Buhmann, 2016;Buhmann, Lepori, & Ingenhoff, 2017).…”
Section: Measuring Research Units Through Their Activities: Methodolomentioning
confidence: 99%
“…Data for this analysis refers to the period 2009-2013. To analyze differences between units regarding their orientation to education vs research, we run a factor analysis using four indicators of educational activities (teaching hours and number of theses for both the bachelor's and master's level) and five measures of research activity (total publications, PhD students and graduates, funds from funding agencies and contracts; Lepori et al, 2016).…”
Section: Change At the Level Of Individual Unitsmentioning
confidence: 99%
“…For studies focusing on the organizational level, disciplinary heterogeneity can be controlled through the repartition of students by fields within HEIs (Lepori, Baschung and Probst 2010) or by breaking down outputs by scientific domains (Waltman, Calero-Medina, Kosten, et al 2012). In turn, for studies at the disciplinary or individual level, if becomes now possible to control for organizational characteristics, as a possible explanation of observed differences, for example through the design of multi-level models (Lepori, Wise, Ingenhoff and Buhmann 2016).…”
Section: Conceptual Rootsmentioning
confidence: 99%